2020
DOI: 10.1142/s0217979220500083
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high intense electron beam irradiation on structural and Raman properties of boron carbide micro powder

Abstract: In the presented work, a boron carbide sample with a purity of 99.9%, particle size [Formula: see text]–[Formula: see text]m and a density of [Formula: see text] was used. Boron carbide samples were irradiated with linear electrons in the energy range of 2.5 MeV at the doses of [Formula: see text], [Formula: see text] and [Formula: see text] at room temperature. XRD results show that only in the crystal structure of [Formula: see text] compound, among boron carbide samples irradiated in the dose rate from [For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 36 publications
0
5
0
1
Order By: Relevance
“…The difference may arise from the fact that the experimental B 13 C 2 sample is mixed with various arrangements of icosahedra and chains . Particularly, previous studies showed a possible configuration (B 11 C)­C–B–B, resulting in symmetry breaking. , Tallant et al also mentioned that boron-rich boron carbide is formed by replacing CBC chains with CBB chains. To confirm this, they investigated the effect of varying carbon content in boron carbide using Raman spectroscopy .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference may arise from the fact that the experimental B 13 C 2 sample is mixed with various arrangements of icosahedra and chains . Particularly, previous studies showed a possible configuration (B 11 C)­C–B–B, resulting in symmetry breaking. , Tallant et al also mentioned that boron-rich boron carbide is formed by replacing CBC chains with CBB chains. To confirm this, they investigated the effect of varying carbon content in boron carbide using Raman spectroscopy .…”
Section: Resultsmentioning
confidence: 99%
“…In addition to B 4 C, the vibrational spectra of other boron-rich icosahedral superhard materials have been examined experimentally and theoretically. ,, Measuring Raman spectra of boron carbides with the carbon content of ∼20 to ∼8 atom % is helpful in understanding the substitutional or chemical disorder that characterizes these structurally ordered solids. ,, These measurements demonstrate that the boron carbide composition with carbon content close to 20 atom % consists of B 11 C p icosahedra linked by C–B–C chains. As the carbon content decreases to about 13 atom %, C–B–B chains gradually replace C–B–C chains.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it is possible to transition from the thermal flux function to thermal conductivity, thermal diffusion, heat capacity and thermodynamic parameters. The transition from the thermal flux functions to the thermal conductivity and the temperature dependence of the heat capacity allow explaining the mechanism of the change of the thermodynamic functions [16]. Fig.…”
Section: Thermal Analysismentioning
confidence: 99%
“…С другой стороны, можно перейти от функции теплового потока к теплопроводности, термодиффузии, теплоемкости и термодинамическим параметрам. Переход от функции теплового потока к теплоемкости и температурная зависимость теплоемкости позволяют объяснить механизм изменения термодинамических функций [16]. На рис.…”
Section: термический анализunclassified